Gratuity through Contradiction as an Access to God. About the Implicit Forms of Loving God by Simone Weil - Caum Aregay, Nuria (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The experience of gratuity that Simone Weil develops in her essay Implicit Forms of Loving God is configured by self-denial and consent to the absolute and can be inferred everywhere. Gratuity shows us the fundamental contradiction of our existence and reflects the harmonic structure of reality as a whole. The pythagoric union of opposites, theologically interpreted, allows the author to give a reason to reality. This gratuity through contradiction leads us towards God, because the fullness of being is concerned with relation. Within the Immanent Trinity, union is found together with distinction. The Holy Trinity shows Itself as grateful love in the Creation, Incarnation and Passion, never ceasing to invite us to enter into Its own dynamism. The implicit forms of love become an indirect access to God. Gratuity is the way.
Keywords: Renounce; consent; harmony and Christological mediation